1999
DOI: 10.1046/j.1464-410x.1999.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

The rectal administration of lidocaine gel and tolerance of transrectal ultrasonography‐guided biopsy of the prostate: a prospective randomized placebo‐controlled study

Abstract: The rectal administration of lidocaine has no impact on the tolerance to prostatic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 15 publications
(23 reference statements)
2
83
0
3
Order By: Relevance
“…Efforts have been reported to control biopsy-related pain; rectal anaesthetic gel was ineffective [1] and the value of an analgesic suppository has not been systematically evaluated, although some use it routinely. Periprostatic LA (both the method of introduction and its value) have not been thoroughly evaluated either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been reported to control biopsy-related pain; rectal anaesthetic gel was ineffective [1] and the value of an analgesic suppository has not been systematically evaluated, although some use it routinely. Periprostatic LA (both the method of introduction and its value) have not been thoroughly evaluated either.…”
Section: Discussionmentioning
confidence: 99%
“…This may arise from puncture of the prostatic capsule and stroma, although some men also ®nd the introduction and maintenance of the ultrasound probe within the rectum uncomfortable [5,6]. Previous studies have evaluated the role of anaesthesia (rectal lidocaine gel [1] or periprostatic nerve blockade [5,7]) in improving patient comfort. Of the last two studies only one was a prospective report, but it was a small series [5].…”
Section: Introductionmentioning
confidence: 99%
“…During transrectal prostate biopsy, the role of anesthesia on pain and tolerance is controversial. [1][2][3][4] Four studies, of which three were prospective and randomized, demonstrated a benefit for pain with local anesthesia. [1][2][3]5 However, a prospective randomized study showed no statistically significant difference on pain between local anesthesia and no anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]5 However, a prospective randomized study showed no statistically significant difference on pain between local anesthesia and no anesthesia. 4 The objectives of our study were to evaluate pain and tolerance of transrectal ultrasoundguided biopsy of the prostate without any anesthesia and to identify a correlation between pain and six parameters: patient age, prostate volume, cores number, operator, previous biopsy and first core location (apex or base).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] A review of recent MEDLINE English literature studies that report on complications of transrectal prostate biopsies and list hematochezia as a complication, showed that of 5911 men biopsied only four required admission for observation of hematochezia, three had oversewing of the rectal mucosa within 2 h of the biopsy to stop bleeding and none required transfusion (Table 1). [10][11][12][13][14][15][16][17] This man had an arterial bleeder that opened 5 days after his biopsy; poorly controlled hypertension and the firm bowel movement most likely contributed to the life-threatening hemorrhage. Neovascularization related to his large volume of disease with high Gleason-grade carcinoma may also have contributed to this patient's excessive bleeding.…”
Section: Discussionmentioning
confidence: 99%